Democratizing entrepreneurship? Digital technologies and the internationalization of female‐led SMEs - Pergelova, Albena; Manolova, Tatiana; Simeonova‐Ganeva, Ralitsa; Yordanova, Desislava (My University, 2019)
This study examines how digital technologies affect the international expansion of female‐led small and medium‐sized enterprises (SMEs). Digital technologies have the potential to democratize entrepreneurship by providing access to international market knowledge and facilitating interactions with customers and partners. Building on the original Penrosean specification of the resource‐based view and the notion of versatility of resources, we propose that digital technologies impact positively SME internationalization through the mediation of international market intelligence. Furthermore, we posit that female entrepreneurs will leverage the enabling effects of digital technologies more than their male counterparts. The hypotheses are tested on a representative sample of 300 Bulgarian SMEs. Implications for policy and research are advanced.
Keywords: entrepreneurship; businesswomen; small business; industrial management; digital technology